ACADEMIC INTEGRITY IN THE AI ERA: A PHENOMENOLOGICAL STUDY ON STUDENTS’ ETHICAL STRATEGIES IN RESEARCH PROPOSAL WRITING - Viktor Siumarlata; Judith Ratu Tandi Arrang; Yizrel Nani Sallata (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2026)
The present study aims to investigate the strategies employed by students to uphold academic integrity and demonstrate responsibility when utilizing artificial intelligence tools in the research proposal writing process. A descriptive qualitative design with a phenomenological orientation was utilized in this research. The design was to investigate the lived experiences of participants. The subjects of this study consisted of three intentionally chosen undergraduate students from the English Education Study Program at a university in Toraja. They were engaged in the preparation of research proposals utilizing artificial intelligence support. Data collection involved semi-structured interviews and direct observations. The analysis was conducted through iterative qualitative techniques such as data reduction, coding, theme categorization, data display, and conclusion drawing with verification. The findings reveal ongoing issues related to academic integrity and transparency, particularly regarding the inconsistent citation of sources produced by artificial intelligence and differing approaches to paraphrasing. The findings show that the participants exhibited ethical behavior by paraphrasing and verifying outputs. on the other hand, they also relied heavily on tools without adequate critical assessment, prompting inquiries into accountability for content accuracy. The findings indicate that the ethical application of artificial intelligence in scholarly writing necessitates a combination of ethical understanding and technical proficiency. It follows that educational programs are required to integrate teachings on the ethical utilization of digital resources, while institutions must establish transparent policies to maintain integrity in student writing.